Derrida in Light of Augustinian; Deconstruction and lying (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research had discussed the concept of Augustinian lying in light of the deconstruction reading of Derrida. The one specific goal is to deconstruct and delve deeper into the theory of embedded meaning in the act of lying as it is a linguistic and in tentional act. Based on this, it will orient Focus towards first specifying the concept of lying, Then discussed the frame of saying in lying  to deduce how deconstruction went through the Augustinian text and its inner construction, to finally get to talking about the intention of deception this is basically the criteria against which lying is measured and distinguished from other events of non_ truth. Then the research will tackle those of non_ lying such as joking and the like through this distinction the research will tackle the moral frame via which Augustine analyzed the types of lying. After words, it accumulates its out comes in a conclusion presenting some of the findings as in ideas that are taken as strategies we deduced out of the Derrida's reading of the Augustinian text regarding this concept.